2018
DOI: 10.1016/j.actatropica.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Screening of natural Wolbachia infection in Aedes aegypti, Aedes taeniorhynchus and Culex quinquefasciatus from Guadeloupe (French West Indies)

Abstract: Guadeloupe islands are threatened by several mosquito-borne viruses such as Dengue, Chikungunya, Zika and West Nile virus. It appears essential to look for alternative mosquito control methods such as the incompatible insect technique (ITT) aiming at sterilizing wild females by inundative releases of incompatible males. Before considering the implementation of such a strategy, the characterization of genetic diversity of the endocellular bacterium Wolbachia regarding the local mosquito populations is a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The high Wolbachia infection in Cx. quinquefasiatus from Guadeloupe [35] has been also suspected to confer refractoriness to ZIKV, but experimental studies showed that even when Wolbachia is removed from this mosquito species, ZIKV fails to infect the midgut epithelial cells [20]. Taken together, these results show that Cx.…”
Section: Discussionmentioning
confidence: 98%
“…The high Wolbachia infection in Cx. quinquefasiatus from Guadeloupe [35] has been also suspected to confer refractoriness to ZIKV, but experimental studies showed that even when Wolbachia is removed from this mosquito species, ZIKV fails to infect the midgut epithelial cells [20]. Taken together, these results show that Cx.…”
Section: Discussionmentioning
confidence: 98%
“…7a) confirms previous observations about the broad distribution of Cx . quinquefasciatus populations with Wolbachia as endosymbiotic bacteria in Guadeloupe [39]. This study from Goindin and colleagues reported a 95.8% positive rate of Wolbachia sp.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming more apparent that a variety of factors contribute to this variation, but we have a lack of understanding regarding why some taxa are present in a host, yet others are absent. In mosquitoes and other insects, much effort has been undertaken to characterize the infection status of species and populations for specific endosymbiotic bacteria such as Wolbachia [6][7][8][9], yet few studies have examined the infection prevalence of specific gut-associated bacteria in mosquito vectors. It is evident that several gut-associated bacterial taxa are common between phylogenetically diverse mosquito species [4,5], but less attention has been paid to identifying incompatible hos-microbe associations and the mechanism(s) behind this incompatibility.…”
Section: Introductionmentioning
confidence: 99%